2012
DOI: 10.1177/0040517511420764
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of bending rigidity for laminated fabric with adhesive interlining by a laminate model considering tensile and in-plane compressive moduli

Abstract: The purpose of this study is to predict bending rigidity of laminated fabric with adhesive interlining considered tensile and in-plane compressive moduli. The predicting method considering those moduli was proposed by theoretical derivation based on laminate model. Tensile and in-plane compressive moduli of neutral surface for face fabric and adhesive interlining respectively before laminating and modulus for bending rigidity were considered independently. The calculating equation for in-plane compressive modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Adhesive interlining is fused to the face fabric and maintains the garment form. It is known that mechanical properties of the face fabric such as the bending rigidity and shear stiffness are affected by fusing interlining [4][5][6][7][8][9]. It is thus necessary to select an appropriate interlining by taking into account these changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesive interlining is fused to the face fabric and maintains the garment form. It is known that mechanical properties of the face fabric such as the bending rigidity and shear stiffness are affected by fusing interlining [4][5][6][7][8][9]. It is thus necessary to select an appropriate interlining by taking into account these changes.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus necessary to select an appropriate interlining by taking into account these changes. Kim et al [4][5][6][7][8][9] studied a method of predicting the bending rigidity and shear stiffness of a laminated fabric comprising an adhesive interlining and face fabric.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the incorporation of adhesive interlining affects the bending rigidity and shear stiffness of laminated fabric [6,7,[12][13][14]. Kim et al [8][9][10][11] proposed the laminate theory of bending and experimental methods to predict the bending rigidity of laminated fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated the changes in bending rigidity and shear stiffness associated with bonding adhesive interlining [1][2][3][4][5]. The effect of adhesive interlining on jacket appearance was investigated by Kim et al [6], who found that the surface smoothness and waist line and thus the appearance of a jacket were affected by bonding adhesive interlining.…”
Section: Introductionmentioning
confidence: 99%